HOW IS THE ESG FACTOR RELATED TO TRADITIONAL FACTORS? - Ngo, Tam Thi; Zárybnická Žárová, Marcela, 1959-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2020)
This master thesis discusses ESG effect on the portfolio performance and how this factor is relatedto conventional factors. First, ESG-related portfolios and the ESG factor portfolio are constructedbased on ESG score. Second, return, standard deviation and Sharpe ratio are calculated to presentportfolio performance. Finally, 12 asset pricing models are run on the portfolio and single-stockslevel. ESG factor is added into base models. We observe that the higher ESG-scored portfolio doesnot lead to the better return compared to the lower ESG-scored portfolio. The analysis of assetpricing models on the portfolio level shows that the ESG factor does not enhance the explanatorypower of traditional models. The analysis on single stocks illustrates that ESG factor can explainexpected return better higher than CMA only, but worse than MKT, SMB+HML, WML, RMWand RMW+CMA.
Vedoucí práce: Marcela Zárybnická Žárová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses